Reading T.S. Eliot: four quartets and the journey towards understanding - Atkins, George Douglas (Palgrave Macmillan, 2012)
"This book offers an exciting new approach to T. S. Eliot's Four Quartets as it shows why it should be read both closely and in relation to Eliot's other works, notably the poems The Waste Land, "The Hollow Men," and Ash-Wednesday. In Four Quartets, Incarnation is the universal, timeless pattern, the paradigmatic instance of which occurs in and as the Incarnation"-- Provided by publisher.